Dirichlet's Theorem in Function Fields. (1st June 2017) - Ganguly, Arijit; Ghosh, Anish
Abstract: We study metric Diophantine approximation for function fields, specifically, the problem of improving Dirichlet's theorem in Diophantine approximation.